PENGGUNAAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER STRUCTURE UNTUK MENINGKATKAN HASIL BELAJAR MATA KULIAH HUKUM ACARA PERDATA PADA MAHASISWA PRODI PPKN FKIP UNIVERSITAS RIAU - Zahirman, Zahirman; Haryono, Haryono; Separen, Separen (Pelita Bangsa Pelestari Pancasila, 2018)
This research aims to improve student results PPKn FKIP UR in the course of civil law, which is the subject of this research is the students of PPKn FKIP UR Semester III totaling 35 people composed of 11 men and 24 women. Process improvements in the research study will use a learning model Numbered Heads Together Structure to see its influence on learning outcomes. Activity faculty and students in the use of this model will be assessed by the observer.            Based on the results of the study showed that the activity of a lecturer in the first cycle with a score of 32 categories of "Perfect" and the increase in cycle II score of 36 in the category "very perfect". For students in the first cycle of activity score of 204 in the category "High" and the second cycle increased to 228 with the category of "very high". While the learning outcomes of students in the first cycle with the category of "Very High" as many as 7 people (20%) and "High" as many as 23 people (66%) increased in the second cycle category of "Very High" as many as 12 people (34%) and "High "as many as 17 people (49%). It can be concluded that the usage learning model Numbered Heads Together Structure can improve learning outcomes in subjects of Civil Law at the FKIP PPKn University of Riau.